2012
DOI: 10.1103/physrevb.86.035416
|View full text |Cite
|
Sign up to set email alerts
|

Modeling evaporation, ion-beam assist, and magnetron sputtering of thin metal films over realistic time scales

Abstract: A long time scale dynamics technique has been used to model the evaporation, ion-beam assist and magnetron sputtering of thin metal films over realistic time scales. Two fcc metals have been investigated; silver and aluminium. We illustrate how the technique can be used to model growth of these films over experimental time scales, while investigating individual growth mechanisms and surface diffusion events. Long time dynamics is achieved through an on-the-fly Kinetic Monte Carlo method, which determines diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…In the case of Ag growth on Ag, it was these concerted motions that could explain the formation of twin boundaries 12 and in the case of ZnO growth how chains of atoms on the surface could move concertedly to form into hexagons. 13 It was therefore surprising to discover that as the silver deposits, there were only a few examples of concerted motion.…”
Section: Akmc Simulations On a Perfect Zno(0001) Surfacementioning
confidence: 99%
See 4 more Smart Citations
“…In the case of Ag growth on Ag, it was these concerted motions that could explain the formation of twin boundaries 12 and in the case of ZnO growth how chains of atoms on the surface could move concertedly to form into hexagons. 13 It was therefore surprising to discover that as the silver deposits, there were only a few examples of concerted motion.…”
Section: Akmc Simulations On a Perfect Zno(0001) Surfacementioning
confidence: 99%
“…Previous simulations of Ag growth on Ag have also shown that the diffusion barriers in the layers are smaller than the barriers to drop down although with a smaller relative difference than calculated here. 12 …”
Section: B Transition Barriersmentioning
confidence: 99%
See 3 more Smart Citations